2022
DOI: 10.1159/000527786
|View full text |Cite
|
Sign up to set email alerts
|

Natural Age-Related Slow-Wave Sleep Alterations Onset Prematurely in the Tg2576 Mouse Model of Alzheimer’s Disease

Abstract: Introduction: Sleep insufficiency or decreased quality have been associated with Alzheimer’s disease (AD) already in its preclinical stages. Whether such traits are also present in rodent models of the disease has been poorly addressed, somewhat disabling the preclinical exploration of sleep-based therapeutic interventions for AD. Methods: We investigated age-dependent sleep-wake phenotype of a widely used mouse model of AD, the Tg2576 line. We implanted electroencephalography/ electromyography headpieces int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Interestingly, we observed a lower number of auditory triggers delivered during NREM in TG AD mice in relation to WT AD . This observation aligns with the previously reported reductions in NREM sleep during the dark period and number of slow oscillations in 7-month-old TG AD mice of the Tg2576 line (Kollarik et al, 2022). Contrastingly, we observed a greater number of triggers during NREM sleep in TG PD mice in relation to WT PD .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, we observed a lower number of auditory triggers delivered during NREM in TG AD mice in relation to WT AD . This observation aligns with the previously reported reductions in NREM sleep during the dark period and number of slow oscillations in 7-month-old TG AD mice of the Tg2576 line (Kollarik et al, 2022). Contrastingly, we observed a greater number of triggers during NREM sleep in TG PD mice in relation to WT PD .…”
Section: Discussionsupporting
confidence: 93%
“…AD mice present heightened NREM sleep fragmentation accompanied by a decrease in NREM sleep duration compared to WT animals (Kollarik et al, 2022). Increased sleep fragmentation is a distinctive feature of neurodegenerative diseases, being linked to accelerated microglia and astrocyte aging and activation, cognitive impairment in patients, increasing amyloid-beta deposition, tau phosphorylation and neuroinflammation, and decreasing AQP4 expression in older AD animals (Cai et al, 2019; Kaneshwaran et al, 2019; Vasciaveo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the onset and time course of sleep changes from preclinical AD to the onset of mild cognitive impairment in human patients is yet to be defined, animal studies revealed sleep alterations already at prodromal AD-stages. Six-month old Tg2576 mice (amyloid mouse model) showed increased wakefulness and decreased sleep 14 prior to amyloid plaque deposition 15 and microglial activation 16 . Further, five-week-old Tg2576 mice showed early hyperexcitability in REMS marked by interictal spikes 17 , a finding paralleled by another study that observed hypersynchronous network activity 18 , underlining the early sleep disturbances linked to β-amyloid neuropathology in this model 17 .…”
Section: Introductionmentioning
confidence: 99%